A hedonic analysis of factors impacting the value of planters on the used machinery market. (22nd August 2022) - Allison, John; Mark, Tyler B.; Burdine, Kenneth H.; Shockley, Jordan M.
Abstract: A hedonic model was employed to examine factors that influence the resale price of row crop planters on the used machinery market. Planter sale data from 2016 to 2018 were utilized to conduct the analysis. Results suggested that the primary factors impacting planter resale prices were make, age, condition, planter configuration, row number, and row spacing. As a function of age (depreciation), planter values were generally determined to decrease at a decreasing rate. Finally, it was determined that there was a significant interaction between the variables make and age, suggesting that different planter makes depreciate differently.